WAYS TO DEVELOP PEDAGOGICAL COMPETENCE IN FOREIGN LANGUAGE TEACHING - Shoimov, Shavkat (Журнал иностранных языков и лингвистики, 2020)
THIS ARTICLE IS ABOUT WAYS TO DEVELOP PEDAGOGICAL COMPETENCE IN FOREIGN LANGUAGE TEACHING